Escaping Poverty through Tricycle Business Operations in Jalingo Metropolis, Taraba State, Nigeria - Enganya, Yakubu; Yerima, Mary; Maikomo, John Moses; Dabale, Jesse Dearsley (International Journal of Education, Culture, and Society, 2025)
Poverty today has become one of the biggest global challenges facing mankind. Global poverty statistics shows that the percentage of people living in extreme poverty has not declined especially in Third World countries. In Nigeria, recent data from the National Bureau of Statistics have shown that over 40%, which represents 82.9 million people lived below poverty line. Taraba state presently occupies 2nd position in poverty level among the 36 states of the federation with poverty prevalence put at 87.72%. Tricycle operations, otherwise known as Keke-NAPEP as an interventionist scheme, was introduced in 2012 to reduce incidence of poverty in the state, though initially tailored towards addressing rising insecurity but eventually metamorphosed into reduction in unemployment and poverty in the process. As it stands today, well over 13,000 registered tricycles are providing intra-city commercial operations in Jalingo metropolis. This study aims at interrogating the relationship between tricycle business operation and poverty alleviation in Taraba state. Has tricycle business operation caused a reduction in poverty among operators? What are the challenges faced by tricycle operators? The study adopted the Marxian Political Economy approach as a theoretical model. The study discovers that there’s a significant improvement in income generation by tricycle operators which consequently reduces poverty among them. Therefore, the study recommends that government should get directly involved in tricycle business by making provisions for more tricycles for operators at subsidized rates in order to strengthen and sustain its anti-poverty measures in the state.